Highly Diluted Antibodies to eNOS Restore Endothelium Function in Aortic Rings From Hypertensive Rats - Nataliya V. Petrova; Sergey A. Tarasov; Oleg I. Epstein; Caroline Dubroca; Thierry Sulpice (SAGE Publishing, 2022)
Background Nitric oxide (NO) as a vaso- and cardio-protective agent could reduce vasomotor dysfunction in different cardiovascular diseases. One of the current therapeutics targeted at NO availability in the vascular wall are highly diluted antibodies to endothelial NO-synthase (eNOS). This drug has previously shown its endothelium-protective effect and effectiveness in reducing hypertension. Current study was dedicated to evaluate the direct impact of highly diluted antibodies to eNOS on the vessel constriction and dilation ex vivo. Methods For that purpose, we used thoracic aortas dissected from spontaneously hypertensive (SHR) rats. Endothelium-dependent relaxation in the presence of highly diluted antibodies to eNOS (1 mL) was examined after phenylephrine-induced pre-constriction of the aorta rings in response to gradually increased acetylcholine concentration (1 nM to 10 µM). Results Highly diluted antibodies to eNOS enhanced acetylcholine-induced relaxation in a statistically significant manner. Moreover, it was demonstrated that observed effect was similar to perindopril, a well-known angiotensin-converting-enzyme inhibitor, which works through relaxing and widening blood vessels. Conclusions Our findings indicate that highly diluted antibodies to eNOS restored impaired endothelium function, as demonstrated by increased relaxation of SHR rats aorta rings. The revealed results suggest beneficial effect of highly diluted antibodies to eNOS to ameliorate hypertension and related diseases.